Disseminated Mycobacterium marinum Infection With a Destructive Nasal Lesion Mimicking Extranodal NK/T Cell Lymphoma: A Case Report. Issue 11 (March 2016) - Asakura, Takanori; Ishii, Makoto; Kikuchi, Taku; Kameyama, Kaori; Namkoong, Ho; Nakata, Noboru; Sugita, Kayoko; Tasaka, Sadatomo; Shimizu, Takayuki; Hoshino, Yoshihiko; Okamoto, Shinichiro; Betsuyaku, Tomoko; et al.
Abstract : Abstract: Mycobacterium marinum is a ubiquitous waterborne organism that mainly causes skin infection in immunocompetent patients, and its disseminated infection is rare. Extranodal NK/T cell lymphoma, nasal type (ENKL) usually localizes at the nasal and/or paranasal area, but occasionally disseminates into the skin/soft tissue and gastrointestinal tract. Compromised immunity is a risk factor for developing nontuberculous mycobacterial (NTM) infection and malignant lymphoma, and the 2 diseases may share similar clinical presentation; however, only a few reports have described NTM infection mimicking malignant lymphoma. A 43-year-old Japanese man presented to our hospital complaining of multiple progressive skin nodules and purulent nasal discharge for 3 weeks. He was diagnosed with Crohn disease with refractory enteropathic arthritis and has been treated with anti-tumor necrosis factor alpha agents for 25 years. Fiberoptic nasal examination revealed septal perforation with hemorrhagic mucus and purulent rhinorrhea. Histological examination of the nasal septum revealed the infiltration of atypical medium-to-large-sized cells with erosion. The cells were positive for cytoplasmic CD3, granzyme B, and Epstein–Barr virus-encoded small RNA. Histological examination of the skin nodules and auricle also showed infiltration of atypical lymphocytes. The patient was tentatively diagnosed with ENKL, and chemotherapy was considered. However, the skin lesions decreased in size after discontinuation of immunosuppressive agents and minocycline administration. Two weeks later, nasal septum and lavage fluid and left leg skin cultures were positive for M marinum, and minocycline was discontinued. The skin and the nasal lesions improved after 2 months. To the best of our knowledge, this is the first case of disseminated M marinum infection with a destructive nasal lesion mimicking ENKL. The differentiation between M marinum infection and ENKL is clinically important because misdirected treatment leads to a poor prognosis. NTM infections including M marinum should be considered in differential diagnosis of ENKL. Bacterial cultures, pathological analysis, and close monitoring are required for the differentiation of ENKL and disseminated M marinum infection; both are serious diseases and early diagnostic distinction between them and immediate appropriate treatment will improve the patient's prognosis.